Software Architectures Evolution based Merging - Bouras, Zine Eddine; Maouche, Mourad (Informatica, 2017)
During the last two decades the software evolution community has intensively tackled the software merging issue. The main objective is to compare and merge, in a consistent way, different versions of software in order to obtain a new version. Well established approaches, mainly based on the dependence analysis techniques on the source code, have been used to bring suitable solutions. However the fact that we compare and merge a lot of lines of code is very expensive. In this paper we overcome this problem by operating at a high level of abstraction. The objective is to investigate the software merging at the level of software architecture, which is less expensive than merging source code. The purpose is to compare and merge software architectures instead of source code. The proposed approach, based on dependence analysis techniques, is illustrated through an appropriate case study.